2022
DOI: 10.47743/saeb-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Advancement in Information Communication Technologies and its Prospect under the role of Aggregate and Disaggregate Globalization

Abstract: Globalization has been witnessed to bring numerous benefits to the advancement in information communication technologies. However, to analyze this relationship mostly aggregate globalization and country-specific studies have been conducted, without considering the importance of disaggregate globalization for advancement in information communication technologies. Therefore, this article aims to examine the impact of aggregate and disaggregate globalization on the advancement of information and communication tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Beta average growth convergence indicates a negative relationship between the initial level of gross domestic product (GDP) per worker and its growth rate (Ray, 1995). This hypothesis posits that, in the long run, GDP per capita in all countries converges to the same growth path (Sorensen et al, 2005;Audi et al, 2023).…”
Section: A) Beta Convergencementioning
confidence: 99%
“…Beta average growth convergence indicates a negative relationship between the initial level of gross domestic product (GDP) per worker and its growth rate (Ray, 1995). This hypothesis posits that, in the long run, GDP per capita in all countries converges to the same growth path (Sorensen et al, 2005;Audi et al, 2023).…”
Section: A) Beta Convergencementioning
confidence: 99%
“…Macroeconomic conditions have a direct and indirect impact on the socioeconomic development of the country (Ali and Naeem, 2017;Ali, 2011;Ali, 2015;Ali, 2018;Ali and Bibi, 2017;Ali and Ahmad, 2014;Ali and Audi, 2016;Ali and Audi, 2018;Ali and Rehman, 2015;Ali and Senturk, 2019;Ali and Zulfiqar, 2018;Arshad and Ali, 2016;Ashraf and Ali, 2018;Audi et al, 2022;Audi and Ali, 2016;Haider and Ali, 2015;Kaseem et al, 2019;Roussel et al, 2021;Sajid and Ali, 2018;Senturk and Ali, 2021;Ahmad et al, 2022;Sulehri and Ali, 2020;Audi et al, 2020;Alim et al, 2022). Macroeconomic indicators, such as GDP, money supply, interest rate, inflation rate, and exchange rate, are considered the fundamentals that drive market movements, and each of these variables is perceived to be unbiased (Francis and Soffer, 1997).…”
Section: The Modelmentioning
confidence: 99%
“…For instance, Myovella et al (2021) identified determinants such as digital infrastructure, GDP per capita, gross capital formation, political stability, regulatory efficiencies, access to electricity infrastructure, government consumption, and trade openness. Audi et al (2022) Researchers argue that previous studies on the determinants of digital technology development have been insufficient, citing issues with empirical methods, approaches, and geographical focus.…”
Section: Introductionmentioning
confidence: 99%